Urodynamics made easy - Chapple, Christopher R.; Hillary, Christopher J.; MacDiarmid, Scott A.; Patel, Anand
The Fourth Edition of Urodynamics Made Easy provides a concise and user-friendly guide to the principles and clinical practice of urodynamics as applied to the routine diagnosis and management of patients. The emphasis of this book is on the ethos behind the practice of urodynamics and how this needs to be integrated into the evaluation of all patients with lower urinary tract symptoms. It offers clear information presented in a visually appealing and easily accessible format.